Assessment of Occupational Competence of Deaf and Hard of Hearing Individuals - Šešum, Mia M.; Radić Šestić, Marina N.; Isaković, Ljubica S. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
When choosing a future profession, it is important for deaf and hard of hearing (DHH) students to be aware of the limitations that can be caused by a hearing loss. However, due to common prejudices, factors such as gender of a DHH person or the prestige level of the desired profession, can also be perceived as limiting. This paper deals with the assessment of occupational competence of DHH men and women made by DHH primary and secondary school students, in relation to the assumed occupational prestige and the required level of communication. The sample consisted of 97 DHH students of the last two grades of primary, and all grades of secondary schools for DHH students in Serbia. The adapted version of the “Evaluation of occupational competence” (EOC) scale (Sela & Weisel, 1992, according to Weisel & Cinamon, 2005) used in this study was further adapted for testing in Serbia. The results obtained after data analysis indicate the existence of significant differences in assessing occupational competence of DHH men and women in relation to occupational prestige and the required level of communication.